Effect of Leadership, Work Environment and Compensation on Employee Performance of PT. Glory Industrial Semarang - Monica Rizma Adventia; Kasmari Kasmari (Budapest International Research and Critics University, 2022)
This study was conducted to find out how the influence between leadership, work environment and compensation with employee performance at PT. Glory Industrial Semarang whether it can have a good impact on the performance of HR. In this study, the authors analyze what are the factors that affect employee performance from year to year. The background behind making this paper is the phenomenon of a decline in the company's production from 2018 to 2020. To obtain the sample itself by means of a non-probability sampling technique, the type is purposive sampling. Subjects that will be targeted are 100 employees of PT. Glory Industrial Semarang. Data was collected through observation by going directly to the location in question and also through questionnaires which were distributed directly to employees as many as 100 copies using a Likert scale. The calculation of data analysis here is through multiple linear regression tests. In this study, it can be taken: (1) Leadership has a positive influence on employee performance with a significance level of t0.000 t< t0.05. (2) Work environment has a positive influence on employee performance with a tsignificant tof t0.030 t< t0.05. (3) Compensation has a positive influence on employee performance with a tsignificance t0.003 t< t0.05. Where from the three variables shows that thypothesis tin tresearch tthis tHo rejected tand tHa taccepted, so that the three independent variables proved to have a positive influence on one dependent variable, namely the performance of employees.